Spółki handlowe a znowelizowana ustawa o kształtowaniu ustroju rolnego – uwagi z praktyki notarialnej - Muszalska, Małgorzata (Studia Prawa Publicznego, 2020)
The article deals with the problems encountered by commercial companies and their partners related to applying the provisions of the Act of 11 April 2003 on the structuring of the agricultural system following the amendment to this Act, which came into force on 26 June 2019. These problems concern the acquisition of agricultural real estate by commercial companies and the disposal of shares and stocks in capital companies already owning such real estate. In the latter case, issues relating to the State Treasury’s (the National Agricultural Support Centre) pre-emptive right and the right to acquire shares and stakes are analysed. The problems here relate mainly to the new procedure introduced by the amendment in question, including new obligations for the company’s management board. Furthermore, there is a discussion of the right of the State Treasury to acquire real estate of partnerships in the event of a change of partner or the accession of a new partner to such a company, as well as the new right to acquire the real estate of a company whose shares are permitted for organised trading. The study advances the thesis that while several facilitating measures have been introduced regarding the acquisition of agricultural real estate by commercial companies, the procedure related to the sale of shares of these companies has been complicated and prolonged to a significant degree. An obligation has been imposed on the management board of a company to collect numerous written documents and send them to the National Centre when the latter has the pre-emptive right or the right to purchase shares or stocks. This impacts negatively on the legal situation of the shareholder whose rights are transferred due to the lack of a deadline by which the company’s management board should submit the agreement to the National Centre. At the same time, the new procedure significantly lengthens the proceedings, generates costs and, above all, is completely unnecessary, as most documents are available in an electronic form. The National Centre also has access to the remaining documents. The new regulations have equipped it with the authority to inspect the books and documents of the company whose shares are being sold.